Muscle metabolic responses and fatigue mechanisms during moderate-, heavy- and severe-intensity cycling exercise - Black, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The sub-maximal exercise intensity continuum comprises three domains - moderate, heavy and severe. The upper limit of the moderate domain is indicated by the lactate threshold (LT) and the boundary between the heavy and severe domains is given by the critical power (CP). The neuromuscular and the muscle metabolic responses that characterise these domains have largely been investigated during small muscle mass exercise, and have not been measured in synchrony. The purpose of this study was to characterise the neuromuscular and muscle metabolic responses during cycling exercise in all three sub-maximal exercise intensity domains. We tested the hypothesis that the muscle metabolic perturbation and fatigue mechanisms would differ between moderate, heavy and severe exercise intensity domain. Methods: Following ethical approval, 10 recreationally active males completed a minimum of four constantwork rate (CWR) severe intensity trials, a heavy intensity CWR trial, and a moderate intensity CWR trial in a randomised design. All trials were performed until task failure or a maximum of 6 h. Venous blood samples were obtained before and during the exercise. Femoral nerve electrical stimulation was used to quantify peripheral evoked responses (M-wave amplitude) in m. vastus lateralis during exercise. Pre- and post-exercise muscle tissue samples (m. vastus lateralis) were collected from 7 subjects. Results: Similar muscle metabolic milieu (i.e., [PCr], [ATP], [lactate] and pH) was attained at exhaustion in all severe intensity trials. Muscle metabolic perturbation was greater (i.e., lower pH and [ATP], and higher [lactate]) at exhaustion following severe compared to heavy intensity exercise (all P<0.05), and also following severe and heavy compared to moderate intensity exercise (all P<0.05). Muscle [lactate] and pH were not different from rest following moderate intensity exercise. Normalised M-wave amplitude was correlated with the changes from baseline to end-exercise in muscle [ATP] (r=-0.41), [lactate] (r=0.54), and pH (r=-0.52), and plasma [K+] (r=-0.34) and blood [lactate] (r=-0.34) across all exercise intensities (all P<0.05). Discussion: These findings provide novel insight into the in-vivo relationship between metabolic perturbation, neuromuscular function and exercise performance. The results support the notion that the LT and CP separate exercise intensity domains within which exercise tolerance is limited by discrete fatigue mechanisms